FAKTOR-FAKTOR YANG MEMPENGARUHI NILAI PERUSAHAAN NON KEUANGAN YANG TERDAPAT DI BURSA EFEK INDONESIA - Deasy Putri; Edric Kurniadi (E-Jurnal Akuntansi TSM, 2022)
This study aims to examine the factors that affect the value of companies in non-financial companies in Indonesia. There are seven independent variables in this study, including: dividend policy, managerial ownership investment opportunity, leverage, profitability, firm size, earnings per share. Fifty eight companies listed during the period 2014-2016 in Indonesia were selected as samples using purposive sampling method. And data analysis is done by using multiple linear regression method. The results of this study indicate that there is a positive effect of dividend policy, profitability, company size, earnings per share on the value of the company. While investment opportunity, managerial ownership, and leverage have no effect on company value